2016
DOI: 10.4254/wjh.v8.i31.1318
|View full text |Cite
|
Sign up to set email alerts
|

Safe and effective sofosbuvir-based therapy in patients with mental health disease on hepatitis C virus treatment

Abstract: AIMTo study impact of baseline mental health disease on hepatitis C virus (HCV) treatment; and Beck’s Depression Inventory (BDI) changes with sofosbuvir- and interferon-based therapy.METHODSThis is a retrospective cohort study of participants from 5 studies enrolled from single center trials conducted at the Clinical Research Center of the National Institutes of Health, Bethesda, MD, United States. All participants were adults with chronic HCV genotype 1 infection and naïve to HCV therapy. Two of the studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 33 publications
(47 reference statements)
9
26
1
Order By: Relevance
“…Previous studies included more therapy‐naive patients with presumably shorter infection times. Concerning depressive symptoms under DAA treatment, the depression scores reduced by 50% in this study, whereas in another study a reduction of only 20% was described …”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Previous studies included more therapy‐naive patients with presumably shorter infection times. Concerning depressive symptoms under DAA treatment, the depression scores reduced by 50% in this study, whereas in another study a reduction of only 20% was described …”
Section: Discussioncontrasting
confidence: 72%
“…Concerning depressive symptoms under DAA treatment, the depression scores reduced by 50% in this study, whereas in another study a reduction of only 20% was described. 39 Our findings could have important implications for HCV-infected patients, since many suffer from impaired quality of life. 6,7 A current survey reported that HCVinfected patients are four times more likely to develop depression in comparison with the general population.…”
Section: F I G U R E 3 Severity Of Depression According To Total Bdi-iimentioning
confidence: 76%
See 2 more Smart Citations
“…The model was parameterised using Phase I and II trials that included telaprevir, and subsequently used to accurately predict sustained virological response rates in Phase II and III trials [13]. This has since been confirmed in the clinic [8,15,16]. This has since been confirmed in the clinic [8,15,16].…”
Section: Application Of Models To Optimise Interferon-antiviral Smallmentioning
confidence: 99%